2022
DOI: 10.1002/iid3.715
|View full text |Cite
|
Sign up to set email alerts
|

The frequency of CD4+ and CD8+ circulating T stem cell memory in type 1 diabetes

Abstract: Introduction:The frequencies and functions of T stem cell memory (TSCM) subsets vary in autoimmune diseases. We evaluated the frequencies of CD4 + and CD8 + TSCM subsets as well as their PD-1 expression levels in patients with T1D. Methods: Blood samples were collected from new case (NC) (n = 15), and long-term (LT) (n = 15) groups and healthy controls (n = 15). Five subsets of T cells including TCM(CD4 + /CD8 + CCR7 + CD45RO + CD95 + ), TCM hi (CD4 + / CD8 + CCR7 + CD45RO hi CD95 + ), TEM(CD4 + /CD8 + CCR7 − … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…Since tumor-associated Ags mainly derive from self-Ags, once T SCM cells trigger antitumor responses, it can ultimately cause autoimmune diseases (1, 2, 4). Notably, Hosokawa et al (34) and our team separately showed that T SCM cells are the least exhausted population than other memory T-cell subsets, which may be due to self-renewal potency and possessing high-length telomeres (34,35). This evidence may justify the chronic and progressive hallmarks of autoimmune disorders.…”
Section: T Scm Cell In Autoimmune Diseasesmentioning
confidence: 78%
See 1 more Smart Citation
“…Since tumor-associated Ags mainly derive from self-Ags, once T SCM cells trigger antitumor responses, it can ultimately cause autoimmune diseases (1, 2, 4). Notably, Hosokawa et al (34) and our team separately showed that T SCM cells are the least exhausted population than other memory T-cell subsets, which may be due to self-renewal potency and possessing high-length telomeres (34,35). This evidence may justify the chronic and progressive hallmarks of autoimmune disorders.…”
Section: T Scm Cell In Autoimmune Diseasesmentioning
confidence: 78%
“…Notably, Hosokawa et al. ( 34 ) and our team separately showed that T SCM cells are the least exhausted population than other memory T-cell subsets, which may be due to self-renewal potency and possessing high-length telomeres ( 34 , 35 ). This evidence may justify the chronic and progressive hallmarks of autoimmune disorders.…”
Section: T Scm Cell In Autoimmune Diseasesmentioning
confidence: 90%
“…Circulating Tscm showed increased frequency in T1DM individuals, thus potentially promoting autoimmunity 74,75 . Hence, their precise role in Cluster B T1DM individuals should be further analysed.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, Tscm play a crucial role in promoting antitumor and immune reconstitution because of their enhanced stem cell-like self-renewal capacity and can serve as a reservoir of effector T-cells. Circulating Tscm showed increased frequency in T1DM individuals, thus potentially promoting autoimmunity 74,75 . Hence, their precise role in Cluster B T1DM individuals should be further analysed.…”
Section: Discussionmentioning
confidence: 99%
“…The production of IFNγ by the peripheral immune system of new-onset T1D patients has revealed contradictory outcomes, most of them have reported a Th1-like phenotype with significantly increased levels of CD4 + and CD8 + subpopulations [35][36][37], while some others have recorded significantly lower percentage of peripheral CD4 + and CD8 + cells producing IFNγ compared to healthy individuals [38]. Therefore, it can be concluded that the imbalance of this cytokine, whether lacking/defective or excessive secretion in the microenvironment, plays an important role in the pathogenesis of the disease.…”
Section: Discussionmentioning
confidence: 99%